Human rights and standard of living in Sub-Saharan Africa : challenges and prospects - Arimoro, Augustine Edobor (Routledge studies in law, rights and justice., 2025)
"This book offers a comprehensive and nuanced examination of the right to an adequate standard of living in Sub-Saharan Africa (SSA), shedding light on the multifaceted challenges, opportunities, and imperatives for action. The right to an adequate standard of living is a fundamental human right, essential for the dignity and well-being of all individuals. Yet, in SSA, the realization of this right remains a complex and elusive goal, with millions of people facing poverty, inequality, and limited access to basic services. Through a series of in-depth chapters, the book explores the various dimensions of the right to an adequate standard of living, from the pervasive impacts of poverty and inequality to the critical importance of access to healthcare, education, housing, and justice. Drawing on a rich array of case studies, data, and expert analysis, the work provides a compelling and evidence-based assessment of the current state of affairs in SSA, highlighting the urgent need for comprehensive and context-specific approaches to advancing this fundamental right. Providing a roadmap for promoting sustainable and inclusive development, reducing poverty and inequality, and ensuring access to basic services for all, the volume offers a set of actionable recommendations for policymakers, practitioners, and researchers working in the areas of Human Rights Law, Development Law and, in particular, those focused on the United Nations Sustainable Development Goals. At the same time, it identifies key areas for further research and investigation, underscoring the importance of ongoing knowledge generation and exchange in support of evidence-based policy and practice"--